1996
DOI: 10.1523/jneurosci.16-24-08140.1996
|View full text |Cite
|
Sign up to set email alerts
|

Central Administration of a Growth Hormone (GH) Receptor mRNA Antisense Increases GH Pulsatility and Decreases Hypothalamic Somatostatin Expression in Rats

Abstract: To test the hypothesis of the involvement of centrally expressed rat growth hormone receptors (rGH-R) in the ultradian rhythmicity of pituitary GH secretion, adult male rats were submitted to a 60 hr intracerebroventricular infusion of an antisense (AS) oligodeoxynucleotide (ODN) complementary to the sequence of rGH-R mRNA. Eight hour (10 A.M.-6 P.M.) GH secretory profiles, obtained from freely moving male rats infused with 2.0 nmol/hr of rGH-R AS, revealed a marked increase in GH peak amplitude (150 +/- 12 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
38
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 37 publications
5
38
1
2
Order By: Relevance
“…It has been demonstrated that GH receptor mRNA is distributed in the hypothalamic nuclei that are involved in GH regulation in rats [12,17,18]. Central administration of GH receptor antisense or antagonist augments spontaneous GH secretion in rats [19,20]. In acute experiments, a bolus injection of human GH to hypophysectomized (HPX) rats induced c-fos gene expression in the hypothalamic arcuate nucleus (Arc) and in the hypothalamic periventricular nucleus (PeV), suggesting that the neurons in these nuclei are the primary targets of GH-autofeedback to the hypothalamus [21].…”
mentioning
confidence: 99%
“…It has been demonstrated that GH receptor mRNA is distributed in the hypothalamic nuclei that are involved in GH regulation in rats [12,17,18]. Central administration of GH receptor antisense or antagonist augments spontaneous GH secretion in rats [19,20]. In acute experiments, a bolus injection of human GH to hypophysectomized (HPX) rats induced c-fos gene expression in the hypothalamic arcuate nucleus (Arc) and in the hypothalamic periventricular nucleus (PeV), suggesting that the neurons in these nuclei are the primary targets of GH-autofeedback to the hypothalamus [21].…”
mentioning
confidence: 99%
“…Although release of SRIF into the median eminence was not measured in FH rats, it is unlikely, on the basis of our present results, that the reported reduced GH response to serotoninergic agonists in FH rats (7,9) could be explained by an enhanced somatostatinergic tone. Reduced mRNA for SRIF in the presence of normal GH and IGF-I concentrations could be the consequence of a defective response of PeN somatostatinergic neurones to GH and IGF-I, or to a reduction in the biological activity of IGF-I, as both hormones exert a positive feedback on PeN somatostatinergic activity (43)(44)(45)(46)(47)(48). The hypothesis of a defective cellular response to GH or IGF-I is compatible with the dramatic reduction of growth that is observed in FH rats.…”
Section: Discussionmentioning
confidence: 71%
“…Since SXN101742 action primarily involves blockade of the exocytic machinery, VAMP cleavage in this case, inhibition of GH synthesis may reflect the existence of an intracellular feedback mechanism in somatotroph cells, linking the failure of GH-containing vesicles to fuse with the plasma membrane to the repression of de novo GH synthesis. Blockade of GH secretion from somatotrophs could also abolish short GH feedback loops known to control GHRH and SRIF hypothalamic production (43)(44)(45), themselves regulating GH synthesis. In any case, this indirect inhibitory action of SXN101742 on GH synthesis could reinforce its therapeutic value compared with current acromegaly treatments.…”
Section: Discussionmentioning
confidence: 99%